The role of multi-stakeholders in the preservation of the Javanese language: Synergy between pawiyatan permadani, universities, and the regency government - Hidayat, Muhtar Sofwan; Firdaus, Firdaus; Najichah, Fatichatun; Ariyani, Mila (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2026)
This study aims to (1) describe the multi-sector contribution to efforts to preserve the Javanese language in Wonosobo Regency, (2) identify inhibiting and supporting factors, and (3) describe strategies to increase the use of Javanese among the younger generation. This research method employs a qualitative approach, utilizing a case study design. Data collection through in-depth interviews, participatory observation, and documentation studies. The research location is Wonosobo Regency, with respondents from the Permadani Pawiyatan Institute, the Tourism Office, and UNSIQ. Data were analyzed using thematic analysis with the help of the NVivo application. This study shows that the preservation of the Javanese language in Wonosobo is the result of a multi-sector collaboration. Permadani plays a role in both the practical and cultural aspects. The local government provides regulatory support and resources, while UNSIQ strengthens the academic aspect. Inhibiting factors: the lack of binding regulations, low motivation of the younger generation, and the dominance of the Indonesian language. Supporting factors: the commitment of related institutions, local policy support, and the role of higher education. The synergy of the three sectors is expected to ensure that the Javanese language remains a proud part of the younger generation’s identity in Wonosobo.